Racial profiling and postmodern society: police responsiveness, image maintenance, and the left flank of police legitimacy - Miller, Kirk (Journal of contemporary criminal justice, 2007)
Racial profiling is among the most important challenges to the legitimacy of law enforcement agencies in the United States. In response to concerns about racial profiling, police departments have taken a number of approaches to address the threat to legitimacy that racial profiling poses. Among the most common approaches, and one that citizens, policy makers, and scholars have all supported, is the implementation of data collection programs designed to document the situational characteristics of traffic stops. The consensus is that data collection will provide an empirical basis for determining whether race-based or other biased policing is occurring. This article argues that this approach is limited in its effectiveness. It is argued that police interest in documenting and preventing racial profiling is driven by concerns about developing and maintaining the perception of responsiveness to the public. Police strategy, ironically, uses technology and science to enhance institutional legitimacy.